Financial fraud detection and big data analytics – implications on auditors' use of fraud brainstorming session. Issue 3 (4th March 2019) - Tang, Jiali; Karim, Khondkar E.
Abstract : Purpose: This paper aims to discuss the application of Big Data analytics to the brainstorming session in the current auditing standards. Design/methodology/approach: The authors review the literature related to fraud, brainstorming sessions and Big Data, and propose a model that auditors can follow during the brainstorming sessions by applying Big Data analytics at different steps. Findings: The existing audit practice aimed at identifying the fraud risk factors needs enhancement, due to the inefficient use of unstructured data. The brainstorming session provides a useful setting for such concern as it draws on collective wisdom and encourages idea generation. The integration of Big Data analytics into brainstorming can broaden the information size, strengthen the results from analytical procedures and facilitate auditors' communication. In the model proposed, an audit team can use Big Data tools at every step of the brainstorming process, including initial data collection, data integration, fraud indicator identification, group meetings, conclusions and documentation. Originality/value: The proposed model can both address the current issues contained in brainstorming (e.g. low-quality discussions and production blocking) and improve the overall effectiveness of fraud detection.